PELATIHAN PADUAN SUARA GITA BAHANA NUSANTARA SECARA DARING DI MASA PANDEMI COVID-19 TAHUN 2021 - Windi Yuliansari Putri, - (2023)
This research is titled "Gita Bahana Nusantara Choir Training Online during the Covid-19 Pandemic Period in 2021." As a community in society, the choir cannot escape the grip of Covid-19 which is so strong. Thus requiring Gita Bahana Nusantara 2021 to appear different from previous years. Therefore, this study aims to reveal the trainer's strategies, member responses, and the results of online training for the Gita Bahana Nusantara Choir during the Covid-19 pandemic in 2021. To obtain data in this study, researchers used qualitative methods through a qualitative descriptive approach with collection techniques in the form of interviews, observation, document study, and literature study. The research subjects used in this study were two trainers and four representatives from each voice (Soprano, Alto, Tenor, and Bass). Based on the results of this research, the Gita Bahana Nusantara choir conducts online training by preparing the training stages that are quite optimal for both trainers and members. However, when viewed from a choral perspective, this online training is not close to optimal and not as effective as meeting face to face. However, the Gita Bahana Nusantara choir was able to maintain the existence of the choir during the Covid-19 pandemic so that its quality was maintained. Keywords: Choir, online training, pandemic